1996
DOI: 10.1259/dmfr.25.2.9446981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instruction on the knowledge, attitudes and beliefs of dental students towards digital radiography.

Abstract: Dental students want digital radiology to be introduced into the dental radiology curriculum, regardless of whether it is examined or not. The teaching methods and content of such a course need careful consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…[7][8][9][10][11] While the literature does include one study that evaluates the effectiveness of web-based instruction in the interpretation of anatomy using CBCT images, 12 no information appears in the literature regarding students' knowledge and attitudes about CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] While the literature does include one study that evaluates the effectiveness of web-based instruction in the interpretation of anatomy using CBCT images, 12 no information appears in the literature regarding students' knowledge and attitudes about CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…The students’ attitudes were very positive towards digital radiography in general, and there were no significant differences between their overall attitudes towards the two digital systems. A previous study has similarly reported that students from two universities, one of which had offered them a didactic course in digital radiography, were similarly favourable towards the use of digital radiography in the dental curriculum, but the students, who had had the course, had higher expectations on the future use of the digital techniques (14). Since that study was undertaken, a few dental schools have switched to digital radiography also for the undergraduate curriculum (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Online learning is becoming a recognized method for delivering educational content throughout dental schools in Northern America. [17][18][19][20] Interactive online learning through web-based courses should also be implemented in dental schools in Turkey, which may transform education from lecture-only courses to student-driven learning.…”
Section: Discussionmentioning
confidence: 99%